Restoration of Flagellar Biosynthesis by Varied Mutational Events in Campylobacter jejuni - Hendrixson, David R. (2008)
Both a complex regulatory cascade involving the FlgSR two-component system and phase variation control expression of σ(54)-dependent flagellar genes in Campylobacter jejuni. In this study, mutational mechanisms influencing production of the FlgS histidine kinase were discovered. Random non-motile, non-flagellated flgS variants were impaired for growth in the chick intestinal tract. Spontaneous revertants restored for flagellar biosynthesis, gene expression, and motility identified by in vivo and in vitro studies had undergone diverse intragenic and extragenic mutational events relative to flgS. Restorative intragenic events included true phase variation, second-site intragenic reversion, and insertion and deletion of short DNA segments within flgS. In vivo-isolated motile revertants possessed an identical, single extragenic mutation to create a partially constitutively-active FlgR protein in the absence of FlgS. Considering that FlgR production is also influenced by phase variation, these new findings suggest that the FlgSR two-component system is a unique in that each protein is controlled by phase variation and phosphorylation. In addition, this study highlights the mutational activities of C. jejuni and suggests that the bacterium may possess a repertoire of mutational mechanisms to overcome genetic lesions that impair production of virulence and colonization determinants while lacking a normal mismatch repair system.